PERANAN PLASMA LUCUTAN PIJAR KORONA TERHADAP PENURUNAN TOTAL BAKTERI SUSU SEGAR - Ali Khamdi; Siti Aminah (Universitas Muhammadiyah Semarang, 2012)
Development of technological applications of plasma as a sterilization system in this case the influence of incandescent discharge plasma towards reduced of total bacteria from fresh milk has been developed and tested. Incandescent corona discharge plasma generated by a point field configuration and the DC voltage (Directing Current) 15 kV, the distance between electrode 2 cm. This system is in sterilizations observation on fresh milk in put in a 5 ml Petri dish in 9 cm and then irradiates the incandescent corona discharge plasma. Variations old incandescent lighting corona discharge plasma with 0 as the control variation 50, 100, 150, 200 seconds. Fresh milk which has been irradiate the incandescent corona discharge plasma at planting on NA medium for amount of total countbacteria. The test results showed that the differences in the old incandescent corona discharge plasma irradiation effect on the number of bacteria in fresh milk. Variations in irradiation time 0 (as control), 50, 100, 150, 200 sec positive correlated to the decrease of total bacterial fresh milk. Plasma irradiation treatment did not alter the pH and color of fresh milk. Key words: milk fresh, the incandescent corona discharge plasma, long irradiation, and total bacteria.